Acceleration of tetrazolium reduction by bacteria. - Bartlett, R C (1976)
Conditions were assessed which would permit more rapid recognition of bacterial growth than has been previously reported using tetrazolium salts. Microtitration trays were used. 2-(p-Iodophenyl)-3(p-nitrophenyl)-5-phenyltetrazolium chloride is rapidly reduced by respiring cells in tissue homogenates but is more toxic than other tetrazoliums when added to growing bacterial cultures. Phenazine methosulfate (PMS), an intermediate electron carrier, potentiates tetrazolium reduction. Growth was readily detected by the addition of these compounds after 3 to 4 h of incubation in Schaedler broth. The final concentration prior to addition to tray wells was 1.0 mg/ml for 2-(p-iodophenyl)-3(p-nitrophenyl)-5-phenyltetrazolium chloride and 0.06 mg/ml for PMS. Addition of 0.5 to 0.8 g of agar per liter of broth enhanced subsequent tetrazolium reduction.